Clinicodemographic profile and predictors of poor outcome in hospitalised COVID-19 patients: a single-centre, retrospective cohort study from India - Prashant K Singh; Lokesh Tiwari; Alok Ranjan; Prakriti Gupta; Prabhat Kumar Singh; Yogesh Kumar; Yankappa N; Amrita Banerjee; C M Singh (BMJ Open)
Objectives Primary objective was to study the clinicodemographic profile of hospitalised COVID-19 patients at a tertiary-care centre in India. Secondary objective was to identify predictors of poor outcome.Setting Single centre tertiary-care level.Design Retrospective cohort study.Participants Consecutively hospitalised adults patients with COVID-19.Primary and secondary outcome measures Primary outcome variable was in-hospital mortality. Covariables were known comorbidities, clinical features, vital signs at the time of admission and on days 3–5 of admission, and initial laboratory investigations.Results Intergroup differences were tested using χ2 or Fischer’s exact tests, Student’s t-test or Mann-Whitney U test. Predictors of mortality were evaluated using multivariate logistic regression model. Out of 4102 SARS-CoV-2 positive patients admitted during 1-year period, 3268 (79.66%) survived to discharge and 834 (20.33%) died in the hospital. Mortality rates increased with age. Death was more common among males (OR 1.51, 95% CI 1.25 to 1.81). Out of 261 cases analysed in detail, 55.1% were in mild, 32.5% in moderate and 12.2% in severe triage category. Most common clinical presentations in the subgroup were fever (73.2%), cough/coryza (65.5%) and breathlessness (54%). Hypertension (45.2%), diabetes mellitus (41.8%) and chronic kidney disease (CKD; 6.1%) were common comorbidities. Disease severity on admission (adjusted OR 12.53, 95% CI 4.92 to 31.91, p<0.01), coagulation defect (33.21, 3.85–302.1, p<0.01), CKD (5.67, 1.08–29.64, p=0.04), high urea (11.05, 3.9–31.02, p<0.01), high prothrombin time (3.91, 1.59–9.65, p<0.01) and elevated ferritin (1.02, 1.00–1.03, p=0.02) were associated with poor outcome on multivariate regression. A strong predictor of mortality was disease progression on days 3–5 of admission (adjusted OR 13.66 95% CI 3.47 to 53.68).Conclusion COVID-19 related mortality in hospitalised adult patients at our center was similar to the developed countries. Progression in disease severity on days 3–5 of admission or days 6–13 of illness onset acts as ‘turning point’ for timely referral or treatment intensification for optimum use of resources.